Movement Ability Intervention Program’s Development Through Rubber Band for Cerebral Palsy Children - Tyas Suciati; Oom Sitti Homdijah (International Inclusion Development and Cooperation, 2023)
The study aims to help children with cerebral palsy through a rubber band media intervention program, with a focus on gross motor skill and fine motor skill aspects. This study uses the Mix Method, which combines data from qualitative and quantitative sources. This research was conducted at SLB X Bandung, and the subject was a student with cerebral palsy. The subject has differences in the size of the hands and the shape of the fingers on one hand which causes difficulty in doing anything related to the right hand, including writing and drawing at school. With this the researcher makes the media according to the needs of the subject. Based on the final data, subjects experienced a significant increase in several aspects. However, the stimulus needs to be given beforehand implementing an intervention program, so that it is easier for the subject to remember numbers and make it easier for the subject the subject worked on a movement ability intervention program. Based on the results above, it can be concluded that the intervention program through rubber bands in cerebral palsy can improve movement abilities.